2021
DOI: 10.1017/s1047759421000453
|View full text |Cite
|
Sign up to set email alerts
|

Grociana piccola: a rare example of Republican military fortifications in Italy

Abstract: Recent investigations at Grociana piccola, a site in northeastern Italy consisting of two sub-rectangular fortifications, offer the rare opportunity to investigate Early Roman military architecture outside the Iberian peninsula. Excavations have revealed an inner rubble masonry rampart dated to the 2nd c. BCE by associated pottery, mainly amphora remains. This date suggests that the fortification was in use during the first Roman conquest and/or later campaigns of the 2nd c. BCE, providing one of the earliest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…According to their typology, the millstones from Povir (POV and POV25), characterized by a considerable height (from about 15 to 25 cm) and a markedly oblique grinding surface, most probably date to the late Republican period. It is worth mentioning that some unpublished first century BCE militaria, such as shoe hobnails of Alesia type D (Bernardini et al, 2021, passim ), are reported from Povir hillfort (Laharnar, personal communication). The larger and flatter lower stone from Bukovica dates to the Imperial period (Fabec & Žerjal, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to their typology, the millstones from Povir (POV and POV25), characterized by a considerable height (from about 15 to 25 cm) and a markedly oblique grinding surface, most probably date to the late Republican period. It is worth mentioning that some unpublished first century BCE militaria, such as shoe hobnails of Alesia type D (Bernardini et al, 2021, passim ), are reported from Povir hillfort (Laharnar, personal communication). The larger and flatter lower stone from Bukovica dates to the Imperial period (Fabec & Žerjal, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…After a first conflict between Rome and the inhabitants of the Istrian peninsula during the late third century BCE, Aquileia was founded in 181 BCE and the area entered under direct Roman influence in the first half of the second century BCE (Bandelli, 2004; Bernardini et al, 2013, 2021; Bernardini & Duiz, 2021; Bernardini, Vinci, et al, 2015). During the Roman period, Euganean trachytic rotary millstones and building material testify to the activation of new commercial routes and the exploitation of previously unexploited quarries (Antonelli et al, 2004; Antonelli & Lazzarini, 2010; Germinario, Hanchar, et al, 2018; Germinario, Zara, et al, 2018; Paltineri et al, 2020; Renzulli et al, 1999; Zara, 2018).…”
Section: Introduction and Archaeological Backgroundmentioning
confidence: 99%
“…The Inner Camp is dated a C14 dating of charcoals from Phase 1, which dates it to the first half of the 2nd century BC. 69 Bernardini 2015: Bernardini 2019; Bernardini et al 2021a. to the 2 nd century BC. Regardless of the use of different building materials (i.e., sandstone vs limestone), its fortification is very similar to that of Phase 1 of San Rocco Camp 1 in the construction technique as well as in dating.…”
Section: Military Architecturementioning
confidence: 99%
“…All of the main features identified in QGIS were checked on the ground through field walking to verify, when possible, their building technique and degradation and to pinpoint potential stratigraphic relations with other structures and possible associated archaeological materials following the methodology developed in other areas of north-eastern Adriatic (Italy, Slovenia and Croatia) and described in previous contributions [5][6][7][8][9][10][11][12].…”
Section: Alsmentioning
confidence: 99%